(R)evolution in the perception of history, national identity and nature in the contemporary Anglo-Guyanese novel - Frątczak, Marta (Wydawnictwo Naukowe UAM, 2016)
Monografia jest w całości poświęcona powieści gujańskiej pisanej w języku angielskim, która nadal jest mało znanym, zarówno w Polsce, jak i na świecie, dyskursem literackim. Wyodrębnia ona powieść tę jako samodzielny i intrygujący przykład powieściopisarstwa wśród innych literatur karaibskich i śledzi jego ewolucję na przestrzeni ostatnich sześćdziesięciu lat. Książka skupia się przede wszystkim na zmianach w gujańskim postrzeganiu historii, tożsamości narodowej i natury oraz znaczeniu powieści dla kształtowania tożsamości karaibskiej i tożsamości narodowych w regionie. Przeprowadzone analizy literackie wpisane są w szerokie tło teoretyczne (studia postkolonialne i ekokrytyczne) oraz kulturalno-społeczne konteksty współczesnych Karaibów.

The book presents an analysis of selected Anglo-Guyanese novels with a view to drawing a map of the Anglo-Guyanese fiction. The main aim of the monograph is to show the Anglo-Guyanese fiction as an intriguing literary discourse that deserves a separate place within the so called Caribbean literary canon. The book touches upon such topics as the relationship between History and historical novel, the impact of the novel on shaping the Guyanese national identity and the original eco-critical dimension the Guyanese discourse of Nature. The monograph may be of interest to those working in the fields of the Caribbean and postcolonial literatures and cultures.
Keywords: Caribbean fiction; Guyanese fiction; postcolonial studies; eco-criticism; powieść gujańska